Analysis of Working Capital in Village-Owned Business Karya Lestari (BUMDes) in the Coastal Area of Bone Bolango Regency - Monoarfa, Rio; Ahmad, Surya Handrisusanto; Latjompo, Sri Mulyani; Djaena, Muhamad A. (Jambura Science of Management, 2025)
Purpose: To determine the amount of working capital measured through the level of cash turnover, inventory turnover, accounts receivable turnover, and working capital turnover in achieving BUMDes profitability.Design/Methodology/Approach: This study uses quantitative research using a descriptive approach. The quantitative data used in this study are figures or documents related to working capital management and profit acquisition at BUMDes Karya Lestari in the coastal area of Bone Bolango Regency.Findings: The data processing carried out shows that BUMDes Karya Lestari's capital requirements for the next period are Rp. 157,916,225. The calculation results show that the capital requirements have increased compared to the previous year.